A review on Snake Bite and Management in Nigeria- The Need for The Development of a Snake Bite Strategy - Babangida, S. , Erhabor, O. , Erhabor, T. , Adias, T.C. (Sokoto Journal of Medical Laboratory Science)
Snake-bites is a global public health and a well-known medical emergency in many parts of the world, especially in rural areas. The aim of this review is to look critically at the challenge of snake Bite in Nigeria and to advocate for the development of a Snake Bite Strategy in Nigeria. The prevention of mortality and morbidity depend upon availability of antivenom in the health facilities in these settings and their rational use. There is the urgent need for the development of a Snake Bite Strategy in Nigeria that takes into account the need for the development of prevention, improved community education, empowerment and effective first response. Mechanisms need to be developed to ensure universal access to antivenom by all needy patients. The Nigerian health system needs to respond to this challenge and logistics must be put in place to ensure timely availability of antivenom at the point of use to prevent preventable disability and death.